Genetic variation and molecular relationships among eight taxa of Desmodium Desv. based on RAPD markers (Bangladesh Journal of Plant Taxonomy, 2017)
Genetic variation and molecular relationships among eight taxa of Desmodium Desv. were assessed on the basis of random amplified polymorphic DNA (RAPD) markers. The banding patterns of eight taxa namely, Desmodium gangeticum (L.) DC., D. heterocarpon (L.) DC., D. heterophyllum (Willd.) DC., D. motorium (Houtt.) Merr., D. pulchellum (L.) Benth., D. triflorum (L.) DC., D. triquetrum (L.) DC. and D. triquetrumsubsp. alatum (DC.) Prain were compared. A total of 81 DNA fragments were detected by 11 primers. Among the taxa studied D. triquetrum and D. triquetrum subsp. alatum were found to be most closely related followed by close proximity between D. gangeticum and D. motorium. The highest genetic distance was observed between D. triflorum and D. heterophyllum followed by D. heterocarpon and D. heterophyllum. UPGMA dendrogram was constructed to show the genetic relatedness among the taxa employed and the tree revealed a close proximity among D. pulchellum, D. gangeticum and D. motorium. In contrast, D. heterophyllum was found distantly related with rest of the taxa.Bangladesh J. Plant Taxon. 24(2): 149–154.